Microstructural Visual Pathway White Matter Alterations in Primary Open-Angle Glaucoma: A Neurite Orientation Dispersion and Density Imaging Study - Haykal, S.; Invernizzi, A.; Carvalho, J.; Jansonius, N.M.; Cornelissen, F.W. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: DTI studies of patients with primary open-angle glaucoma have demonstrated that glaucomatous degeneration is not confined to the retina but involves the entire visual pathway. Due to the lack of direct biologic interpretation of DTI parameters, the structural nature of this degeneration is still poorly understood. We used neurite orientation dispersion and density imaging (NODDI) to characterize the microstructural changes in the pregeniculate optic tracts and the postgeniculate optic radiations of patients with primary open-angle glaucoma, to better understand the mechanisms underlying these changes.MATERIALS AND METHODS: T1- and multishell diffusion-weighted scans were obtained from 23 patients with primary open-angle glaucoma and 29 controls. NODDI parametric maps were produced from the diffusion-weighted scans, and probabilistic tractography was used to track the optic tracts and optic radiations. NODDI parameters were computed for the tracked pathways, and the measures were compared between both groups. The retinal nerve fiber layer thickness and visual field loss were assessed for the patients with glaucoma.RESULTS: The optic tracts of the patients with glaucoma showed a higher orientation dispersion index and a lower neurite density index compared with the controls (P < .001 and P = .001, respectively), while their optic radiations showed a higher orientation dispersion index only (P = .003).CONCLUSIONS: The pregeniculate visual pathways of the patients with primary open-angle glaucoma exhibited a loss of both axonal coherence and density, while the postgeniculate pathways exhibited a loss of axonal coherence only. Further longitudinal studies are needed to assess the progression of NODDI alterations in the visual pathways of patients with primary open-angle glaucoma across time.AUCarea under the curveFAfractional anisotropyFISOfraction of isotropic diffusionLGNlateral geniculate nucleusMDmean diffusivityNDIneurite density indexNODDIneurite orientation dispersion and density imagingODIorientation dispersion indexORoptic radiationOToptic tractPOAGprimary open-angle glaucomaRNFLretinal nerve fiber layerROCreceiver operating characteristicV1primary visual cortexVFMDvisual field mean deviation